Enhancement of fluorescence in inorganic dyes by metallic nanostructured surfaces - Kitsakorn Locharoenrat; Pattareeya Damrongsak (My University, 2016)
We have studied the influence of shape and chemical content of metallic nanostructures (gold-palladium core-shell nanorods, gold nanobipyramids and single-crystalline porous palladium nanocrystals) on the luminescence of Rhodamine 6G and Coumarin153 dyes.The changes found in the emission intensity are attributed to different proportions of the dyes and the metallic nanostructures.The enhancement of the fluorescence observed by us for the cases of Rhodamine 6G with gold-palladium core-shell nanorods and Rhodamine 6G with gold nanobipyramids suggests their promising plasmonic properties.This may be regarded as a preliminary step towards development of the fluorescent probes possessing high photo-sensitivity.
Keywords: Gold and Silver Nanoparticles Synthesis and Applications